Modernization of Thai Fine Art and Its Reflection in Thai National Monuments 1930s- 1940s - Akbar Bagaskara; Septiana Wahyuningsih (ARRUS Journal of Social Sciences and Humanities, 2023)
The purpose of this study is to determine the impact of the modernization of art in Thailand on the reflection of the construction of the Thai national monument range in the 1930s to 1940s. The method used in this research is qualitative, with data sources coming from direct observation, interviews, and scientific documents. The result of this research shows that, the influx of western influence in Thailand indirectly influenced the modernization of the country's art culture. One of the triggers was the number of national academics who were sent to Europe to study, and returned to Thailand with a new artistic ideology. In addition, the influence of Italian artist Silpa Bhirashi also contributed to the modernization of Thai fine art. As it is known, he is one of the curriculum designers in Thai fine art schools and Silpakorn University. On the other hand in the political world, the modernization of Thai fine art was also influenced by the political policies of Marshall Phibunsongkhram who used art as a propaganda tool to unify the ideology of all Thai people.